Visual Outcome after Intravitreal Bevacizumab for Macular Edema Secondary to Branch Retinal Vein Occlusion - Aneeq ullah Baig Mirza, Yasir Iqbal, Sohail Zia (Pakistan Journal of Ophthalmology, 2012)
Purpose: To determine the effect of intravitreal bevacizumab on visual acuity in patients with macular edema secondary to branch retinal vein occlusion Material and methods: This prospective non-randomized clinical interventional study with Convenience (Non Probability) sampling was conducted at Redo Eye Hospital, Rawalpindi; from June 2008 to July 2010. Twenty eyes of twenty patients received a single injection of Bevacizumab in a dose of 1.25 mg/0.05 ml .The visual acuity was measured pre injection and at 4, 8 and 12 weeks post injection using Snellen’s visual acuity chart. Results: At presentation 50% of the patients presented with best corrected visual acuity of 6/60 or worse, 35% were in between 6/60 and 6/24 where as 15 % were 6/18 or better. On the 3rd post injection follow up month 5% of the patients were with best corrected visual acuity of 6/60 or worse , 30 % were in between 6/60 and 6/24 where as 65% were 6/18 or better. The results are statistatically significant (p value less than 0.05). Conclusions: Intravitreal therapy using bevacizumab appears to be an effective treatment for improvement of vision in patients with macular oedema secondary to branch retinal vein occlusion. The positive results though based on short term basis, encourage studies to be conducted on a longer follow up period.